Degradation of naphthalene and pyrene by several biofilm-forming photosynthesis purple bacterial strains - Thi Minh Nguyet, Nguyen; Phuong Ha, Hoang; Van Quyen, Dong; Ngoc Huong Tra, Nguyen; Nhi Cong, Le Thi (Vietnam Journal of Biotechnology, 2020)
Aromatic hydrocarbons such as naphthalene, pyrene are recalcitrant compounds found in oil contaminated areas including petroleum storage tanks, oil exploiting companies. These components are difficult to be degraded/transformed in the lack of oxygen conditions. Among anaerobic and micro-aerobic microorganisms, photosynthetic purple bacteria are the dominant group. Photosynthetic purple bacteria (PPB) are considered as aquatic organisms which are able to grow in anaerobic conditions by photosynthesis but without oxygen. This bacterial group has flexible metabolic types depending on living conditions, then they are widely distributed in nature. There are numerous publications on planktonic PPB which could use naphthalene and pyrene as carbon and energy sources. However, there is no publication on biofilm formed by PPB to degrade their aromatic compounds. In this research, 4 biofilm-forming PPB strains including DQ41, PY2, PY6 and DG12 were screened and estimated their pyrene and napthalene degradation capacity. These organisms demonstrated high biofilm forming ability. As biofilm types, their utilization efficiencies were upper 79% with the initial concentrations of naphthalene and pyrene of 200 and 250 ppm, respectively. These results may contribute to enlarge the number of biofilm-forming microorganisms to degrade/transform aromatic hydrocarbons in polluted area treatment in Vietnam.